The Effect of the Taro Corm Type and Storage on Morphophysiological Deterioration and Early Growth in the Field - Ridwan Diaguna; Edi Santosa; Candra Budiman (International Journal of Agronomy)
Corm type correlates with corm size, which affects longevity and early growth in the field. Seed storage after harvesting is important to preserve viability and vigor. This study was conducted to determine the correlation between the corm type and storage period on corm deterioration, storage, vigor, and growth in the field. A factorial randomized complete block design (RCBD) with three replications was arranged, with the corm size (i.e., corm and cormels) and the storage period (i.e., 0, 2, 4, and 6 weeks). Corms undergo color changes faster than cormels do. The weight and diameter decreased by more than 10–30% after 4 weeks, while the length decreased by more than 10% after 6 weeks, and even the hardness decreased by 50% compared to that at 0 weeks. Corms were stored for 6 weeks, when the weight loss was lower than that of cormels. The corm sprouted after 2 weeks of storage. Corm resulted in a higher sprouting percentage than cormels. The corm type did not have a significant effect on growth vigor, but corm resulted in higher growth vigor than cormels after storage. The storage period leads to growth vigor loss. Weight, length, and diameter loss were positively correlated with sprouting and negatively correlated with hardness and growth vigor. This research recommends that the storage period of taro tubers before planting should be less than six weeks to optimize growth in the field.